High L-Carnitine Levels Impede Viral Control in Chronic Hepatitis B Virus Infection - Gu, Shuqin; Fu, Xin; Ye, Guofu; Chen, Chengcong; Li, Xiaoyi; Zhong, Shihong; Tang, Libo; Chen, Haitao; Jiang, Deke; Hou, Jinlin; Li, Yongyin (Frontiers in Immunology, 2021)
Persistent antigen exposure during chronic hepatitis B infection leads to exhausted immune responses, thus impeding viral control. In recent years, immunometabolism opens new therapeutic possibilities for the modulation of immune responses. Herein, we investigated the immunomodulatory effect of L-carnitine (L-Cn) on immune cells in chronic HBV infection. In this study, 141 treatment-naïve patients with chronic HBV infection, 38 patients who achieved HBsAg loss following antiviral treatment, and 47 patients who suffered from HBV-related HCC from real-life clinical practice were recruited. The plasma L-Cn levels were measured by ELISA. RNA sequencing was conducted to define the transcriptional profiles of peripheral blood mononuclear cells after L-Cn stimulation. In vitro assays were performed to assess the effect of L-Cn on immune cells; the frequencies and function of immune cells were analyzed by flow cytometry. We found that compared with patients with HBsAg loss, patients with HBsAg positivity and patients who suffered from HBV-related HCC had higher levels of L-Cn, and the plasma levels of L-Cn in the HBeAg-positive chronic hepatitis patients who had elevated ALT were significantly higher than that of HBeAg-negative chronic infection and HBsAg loss groups. Moreover, a positive correlation between plasma levels of L-Cn and HBsAg levels was found. Additionally, RNA sequencing analysis demonstrated that L-Cn altered the transcriptional profiles related to immune response. In vitro assays revealed that L-Cn suppressed the proliferation of and IFN-γ production by CD4+ and CD8+ T cells. It also down-regulated the proliferation and IgG production of B cells. Notably, L-Cn enhanced IL-10 secretion from regulatory T cells and up-regulated the expression of inhibitory receptors on T cells. Moreover, a variant in CPT2 (rs1799821) was confirmed to be associated with L-Cn levels as well as complete response in CHB patients following Peg-IFNα antiviral therapy. Taken together, the immunosuppressive properties of L-Cn may hinder the control of HBV in chronic HBV infection, implicating that L-Cn manipulation might influence the prognosis of patients with HBV infection.